A novel series-parallel hybrid robot for climbing transmission tower. Issue 4 (18th May 2021) - Yao, Yanzhang; Wang, Wei; Qiao, Yue; He, Zhihang; Liu, Fusheng; Li, Xuelong; Liu, Xinxin; Zou, Dehua; Zhang, Tong
Abstract : Purpose: The purpose of this paper is to describe the design and development of a novel series-parallel robot, which aims to climb on the transmission tower. Design methodology approach: This study introduces a hybrid robot, which consists of adsorption and two 3-degree of freedom (DOF) translation parallel legs connected by a body linkage. The DOF of the legs ensures that the robot can move on the climbing plane, also contribute to a compact design of the robot. An electromagnet is used to adsorb onto the transmission tower, simplifying the overall structure. Based on the robot design, this paper further defines its climbing gait and adopt the 6th B-spline curves for climbing trajectory planning under different working environments. Findings: The developed prototype that implements the design of the robot, which was used in simulation and experiments, showing that the robot is capable of climbing in the test environments with the planned climbing gait. Originality value: The hybrid robot is able to climb under varying degrees of inclinations and cross the obstacles, and the magnetic attraction can ensure stable climbing.